The Importance of Self-Esteem to Students Learning Responsibilities and Group Learning Commitment of Physical Education Students - Jusuf Blegur; Zuvyati A. Tlonaen; Andreas J. F. Lumba; Julian J. Leko (STKIP Singkawang, 2021)
This study aims to examine the relationship between self-esteem and learning responsibility and group learning commitment of physical education students. We used a quantitative approach, with a correlation design. During the research, there were 88 physical education students from semester VI involved. In collecting the data, we used the State Self-Esteem Scale from Heatherton and Polivy (1991), the Personal Responsibility Questionnaire from Mergler (2007), and the Organization Commitment Scale from Allen and Meyer (1990). The research data were analyzed descriptively and used Pearson correlation with the assistance of SPSS. The descriptive test revealed that self-esteem is quite good (67%), responsibility for learning is relatively good (54.6%), and students’ group learning commitment is quite good (65.9%). Whereas, the Pearson test indicated that there is a positive and significant relationship between self-esteem and learning responsibilities (0.468) and the students’ group learning commitment (0.282). This study emphasizes that lecturers and peers need to support, maintain, and develop positive self-esteem through supportive feedback to encourage students’ learning behavior, such as being responsible and committed to group learning in completing various learning tasks.